Fraktal dan Variabilitas dalam Siklus Bintik Matahari - Dhani Herdiwijaya; Baju Indradjaja (Indonesian Journal of Physics, 2002)
Monthly sunspot numbers during period 1749 to 2000 were used to determine their fractal properties. Lomb’s algoritm and Morlet wavelet were applied to detect the distinct period of 11 year. By using Detrended Fluctuations Analysis (DFA), fractal dimension was measured. It is shown that during the last two centiries, 11-year wavelet amplitude showed doubled increment, in contrast with Gleissberg period. The evolution of fractal dimension varied in between 0.5 to 1.5, which imply that sunspot number time series are nonstationary and correlated to each other within 132-year period. The detected cross-over feature at D=1.3 corresponds to 11-year period and granulation size.